The Effect Of Traininig And Compensation On Employee Performance At Hotel Mercure In Bengkulu City - Ferda Oktavia; Sulisti Afriani; Iswidana Utama Putra (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
The purpose of this study is to determine the effect of training on employee performance, to identify the effect of compensation on employee performance, and to analyze the combined effect of training and compensation on employee performance at Hotel Mercure in Bengkulu City. The results of this study indicate the regression equation Y = 15.637 + 0.109X₁ + 0.463X₂ + e, showing that training (X₁) and compensation (X₂) have a positive effect on employee performance (Y). The coefficient of determination (R² = 0.371) indicates that training and compensation together can explain 37.1% of the variation in employee performance, while the remaining 62.9% is influenced by other factors outside this study.Partial test results show that training has a positive but not significant effect on employee performance (tcount 1.054 < ttable 1.670; sig. 0.296 > 0.05), while compensation has a positive and significant effect (tcount 4.756 > ttable 1.670; sig. 0.001 < 0.05). Simultaneously, the F-test results show that training and compensation have a positive and significant effect on employee performance (sig. 0.001 < 0.05). Overall, improving the training system and providing appropriate compensation can enhance employee performance at Hotel Mercure Bengkulu City.